The Influence Of Audio Visual Media On Increasing Adolescent Women's Knowledge About Anemia At Mts N 2 Districk Rejang Lebong - Maharani, Elsa; misniarti, misniarti; Kurniyati, Kurniyati (Jurnal Kesehatan Saintika Meditory, 2024)
Intoduction: Adolescent females' primary health issue is anemia, which is brought on by inadequate dietary intake. Teenage girls are more susceptible to iron deficiency anemia as a result of menstruation. It is vital to increase teenage girls' understanding of nutrition through education and campaigns that use teen-friendly tactics, in addition to the government's efforts. Videos are one kind of audio-visual material that is used to provide education, among other media. Method: Pre-experiment research is the research design employed, and quantitative research is the research type. The study used a "one group pretest and post-test design," meaning that there is only one treatment group and no control group. The instrument used in this study was a questionnaire, and the sample consisted of 43 teenage girls from MTs Negeri 2 Rejang Lebong. The sample was selected using a stratified random sampling procedure. Chi-Square was the analysis approach employed. Findings and Discussion: With a p value of 0.030 <0.05, the Chi Square test findings indicate a significant effect. With a mean pre-post value of 46 and a mean post-test value of 66, the OR value of 2.877 (1.194-6.934) indicates that there is an increase following the intervention and an increase of 20% from before the intervention. In conclusion, a program utilizing audiovisual (video) health education can be implemented to raise awareness of anemia among teenage females in an effort to prevent it from occurring. Keywords : Teenagers; Anemia; Audio Visual Media